Relationship between Neutrophil-Lymphocyte Ratio and Type of Febrile Seizures Event - Putra, Agus Indra Yudhistira Diva; Mustika, Putu Pradnyanita; Suryawan, Wayan Bikin (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Febrile seizure is a common neurological condition affecting children. Complete blood count (CBC) is often used as the initial test to help determine the etiology of fever based on hematology parameters in the emergency ward.Objective: To analyze the relationship between neutrophil-lymphocyte ratio (NLR) and the type of febrile seizure among pediatric patients admitted to Wangaya General Hospital Denpasar, Indonesia.Methods: A cross-sectional design was implemented on a study using medical records of 44 children aged 6 month-5 years old admitted to the Wangaya Hospital between January 1, 2023, and September 8, 2024. Participants were grouped into simple and complex febrile seizures.Results: Among patients who experienced the first febrile seizure, the complex type accounted for most hospitalizations (n=33, 75.0%). The majority of cases occurred in children aged ≤24 months (n=32, 72.7%) with a temperature of >38°C (n=27, 61.4%). Seizure duration was ≤15 minutes in most cases (n=41, 93.9%), with upper Respiratory Infection being the most common etiology (n=20, 45.5%). NLR did not differ significantly between the simple and complex febrile seizures (P value =0.894), with a prevalence ratio (PR) of 1.1. Additionally, leukopenia, lymphocytopenia, and neutrophilia were observed in 28 (63.6%), 23 (52.3%), and 24 (54.5%) patients, respectively.Conclusion: There is no significant relationship between NLR and the type of first febrile seizures. Seizures are more frequently observed in males, particularly those aged 6-24 months with body temperature exceeding 38°C. The mean NLR of 2.78 ± 2.38 and upper respiratory infection are the most frequently associated conditions.